Evaluation of rubber nursery planting methods, by direct sowing in the field, without seed bed and transplanting - Pereira, Ailton Vitor; Pereira, Elainy Botelho Carvalho (Pesquisa Agropecuaria Brasileira, 1998)
This work was carried out in field conditions, from April to May of 1991, at Goiânia experimental station of the Emgopa, State of Goiás, Brazil. Its objective was to evaluate different methods of planting rubber nursery [Hevea brasiliensis (Willd. ex Adr. de Juss.) Müell. Arg.], by direct sowing in the field, without seed bed and transplanting. The experimental design was a randomised complete blocks, with five replications and five treatments. Beyond the traditional field nursery (control method with seed bed and transplanting), it was tested four other methods of direct sowing of seeds, both in small planting holes and shallow furrows (4-5 cm deep), in which seeds were slightly covered by a thin layer (≤ 2 cm) of both soil and sawdust. Treatments were technically and economically compared based on accumulate percentage of normal seedlings, every five days, from 10 to 40 days after sowing; and labor and material demand. The results showed that, for field nurseries, the method of direct and shallow sowing of rubber seeds and its light covering by soil is technically and economically more efficient than the traditional and other methods tested.